Characterization of the L4-L5-S1 motion segment using the stepwise reduction method (2016)
The two aims of this study were to generate data for a more accurate calibration of finite element models including the L5–S1 segment, and to find mechanical differences between the L4–L5 and L5–S1 segments. Then, the range of motion (ROM) and facet forces for the L4–S1 segment were measured using the stepwise reduction method. This consists of sequentially testing and reducing each segment in nine stages by cutting the ligaments, facet capsules, and removing the nucleus. Five L4–S1 human segments (median: 65 years, range: 53–84 years, SD=11.0 years) were loaded under a maximum pure moment of 8 N m. The ROM was measured using stereo-photogrammetry via tracking of three markers and the facet contact forces (CF) were measured using a Tekscan system. The ROM for the L4–L5 segment and all stages showed good agreement with published data. The major differences in ROM between the L4–L5 and L5–S1 segments were found for lateral bending and all stages, for which the L4–L5 ROM was about 1.5–3 times higher than that of the L5–S1 segment, consistent with L5–S1 facet CF about 1.3 to 4 times higher than those measured for the L4–L5 segment. For the other movements and few stages, the L4–L5 ROM was significantly lower that of the L5–S1 segment. ROM and CF provide important baseline data for more accurate calibration of FE models and to understand the role that their structures play in lower lumbar spine mechanics